Identification of wine related yeast species by capillary electrophoresis single strand conformation polymorphism analysis (CE-SSCP) of the 26S rRNA Gene - Dellinger, B. (2006)
Financially supported by the programs POCI 2010 (FEDER/FCT, POCTI/AGR/56102/2004, POCTI/AGR/56771/2004), and AGRO (ENOSAFE, Nº 762).